Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
The Oxford Handbook of International Antitrust Economics, Volume 2 2015
DOI: 10.1093/oxfordhb/9780199388592.013.0014
|View full text |Cite
|
Sign up to set email alerts
|

Tying Arrangements

Abstract: Tying arrangements, sometimes known as “ties,” “tie-ins,” “tied-in sales,” or “bundles,” occur when a firm offers two separate products together, refusing to sell one of them without the other. Identifying when two things are really a single product—such as a shirt and its buttons or an automobile and its tires—has proven controversial. The dominant position looks at ordinary business practices in order to determine whether the products are commonly sold separately. Competitive harm is a threat in a very few s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…38 To add to the SEC's increasing power, the Dodd-Frank Act authorized the SEC to adopt any rules that reasonably prevented security-based swaps from being traded fraudulently or harmed by deceptive or manipulative practices. 39 This power was to be housed under section 9 of the 1934 Act, 40 instead of section 10(b) of the same statute. It is notable that the burden of proof under section 9 is greater than that described in section 10(b).…”
Section: The Sec's Anti-manipulation Role After Dodd-frankmentioning
confidence: 99%
“…38 To add to the SEC's increasing power, the Dodd-Frank Act authorized the SEC to adopt any rules that reasonably prevented security-based swaps from being traded fraudulently or harmed by deceptive or manipulative practices. 39 This power was to be housed under section 9 of the 1934 Act, 40 instead of section 10(b) of the same statute. It is notable that the burden of proof under section 9 is greater than that described in section 10(b).…”
Section: The Sec's Anti-manipulation Role After Dodd-frankmentioning
confidence: 99%
“…27 Thirdly, the Court would be in good company to dispense with the arcane rule in Illinois Brick, as it would be joining the EU, several US states, and advisory bodies that have all opted for the equal treatment of direct and indirect purchasers: In the EU, as mentioned, Article 3 of the Damages Directive allows "any natural or legal person who has suffered harm caused by an infringement of competition law" to claim damages, and precedent has reiterated time and again that this includes direct and indirect victims. 28 Similarly, more than 20 US states have adopted or interpreted their antitrust laws to allow indirect purchasers to sue, 29 which means that for the same conduct direct purchases can claim damages under federal antitrust law and indirect purchasers can claim damages under state law (assuming the conduct is illegal under both). Recognising the impracticality of Illinois Brick, and following the wave of state antitrust provisions to give standing to indirect purchasers, the US Antitrust Modernization Commission recommended that the rule in Illinois Brick be overruled "to the extent necessary to allow both direct and indirect purchasers to sue to recover for actual damages from violations of the federal antitrust laws."…”
Section: Fragmentation and Strategic Manipulation Of Antitrust Proceedingsmentioning
confidence: 99%
“…242 According to Hovenkamp, '(t)oday the government could do something similar by requiring its departments and agencies to use open-source software as an alternative to Microsoft's products'. 243 This would increase the open source software installed base, as governments are among the principal purchasers of software products, and would help the economy move from a monopolized to a competitive computer platform network. The benefits for innovation would be particularly important, as recent studies have showed that innovative incentives (investments in applications) are sometimes greater for open source than for proprietary software platforms.…”
Section: Public Procurement Procedures As An Antitrust Remedy: Reducimentioning
confidence: 99%